2017
DOI: 10.1515/ijcre-2016-0203
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Congo Red Dye from Aqueous Solutions by Montmorillonite as a Low-cost Adsorbent

Abstract: Abstract:In this study, the sorption of Congo red (CR), as a toxic dye, from aqueous media was investigated using montmorillonite (MMT) as a low-cost adsorbent. The influence of several factors such as contact time, pH, adsorbent dosage, dye content, and ionic strength was investigated on the dye removal. MMT was characterized by Fourier transformed infrared (FTIR) spectroscopy and X-ray diffractometer (XRD). Different kinetic and isotherm models including pseudo-first and pseudo-second order kinetic and Langm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Anionic dyes (i.e., congo red, CR) and cationic dyes (i.e., methylene blue, MB) are the most frequent synthetic dyes found in dye-contaminated water 2,3 . Earlier studies have reported the adverse effect of these dyes for environment and human health, where extended contact may trigger kidney disease, cancer and allergies 4,5 . Due to the severity of dye contamination, several removal methods, such as electrolysis, membrane filtration, photo-assisted degradation, and adsorption, have been developed [6][7][8] .…”
mentioning
confidence: 99%
“…Anionic dyes (i.e., congo red, CR) and cationic dyes (i.e., methylene blue, MB) are the most frequent synthetic dyes found in dye-contaminated water 2,3 . Earlier studies have reported the adverse effect of these dyes for environment and human health, where extended contact may trigger kidney disease, cancer and allergies 4,5 . Due to the severity of dye contamination, several removal methods, such as electrolysis, membrane filtration, photo-assisted degradation, and adsorption, have been developed [6][7][8] .…”
mentioning
confidence: 99%
“…However, adsorption method has proven to be a promising method due to its efficiency, relatively low cost, reusability, and easy operation [9,18]. Congo red adsorption has been reported with adsorbents such as activated carbon with a removal efficiency of about 100% [19], activated carbon prepared from Aloe Vera leaves with a performance of almost 100% [20], jujuba seeds with a dye removal of 88% [21], roots of Eichhornia crassipes with 96% [22], and montmorillonite clay with 85% [23]. The use of solid waste as an adsorbent material has been extensively studied, however, such hazardous waste materials as leather have rarely been applied to this purpose.…”
Section: Adsorbentsmentioning
confidence: 99%
“…Therefore, it is highly important to remove azo dyes from wastewater effluents before discharge into water bodies. Today, the use of adsorbents has increased for removing dyes from the wastewater [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%